The optimal top marginal tax rate: Application to Hungary - Aron Kiss (European Journal of Government and Economics (EJGE), 2013)
The paper applies recent developments in the theory of optimal income taxation to the Hungarian personal income tax system. The main conclusion is that the optimal top marginal tax rate in Hungary is likely to be higher, perhaps substantially, than the actual rate. It is discussed how this result depends on the parameters describing labor-supply behavior, the income distribution, and the redistributive preferences of society.
Keywords: 330; Optimal income taxation; top income tax rate; Hungary; emerging markets